To kill a mockingbird [videorecording (DVD)] - Peck, Gregory, 1916-2003; Peters, Brock; Duvall, Robert; Badham, Mary, 1952-; Lee, Harper (Universal Studios Home Entertainment, 2012)
In a racially divided Alabama town in the 1930s, widowed lawyer Atticus Finch agrees to defend a young black man accused of raping a white woman, teaching his children valuable lessons about prejudice and empathy.